1992
DOI: 10.1007/bf02382746
|View full text |Cite
|
Sign up to set email alerts
|

New records of within-group infanticide and cannibalism in wild chimpanzees

Abstract: ABSTRACT. Two cases of within-group infanticide and cannibalism were observed among the M Group chimpanzees of the Mahale Mountains, Tanzania. In both cases, victimized infants were male, 5 -6 months of age, and in good health when killed. Four to five years have passed since the mothers of the victims immigrated into M Group as nulliparous immigrants. In one case the 2nd-ranking male was observed to detach the infant from the mother's belly. Both infants were finally killed by the alpha male after several adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…This is in contrast to Mahale, where within-community infanticide by males has been a significant cause of death [Nishida et al, 2003]. Many of the infanticide victims at Mahale were offspring of females who joined M-group after the K-group community disappeared [Hamai et al, 1992].…”
Section: Within-community Aggressionmentioning
confidence: 94%
“…This is in contrast to Mahale, where within-community infanticide by males has been a significant cause of death [Nishida et al, 2003]. Many of the infanticide victims at Mahale were offspring of females who joined M-group after the K-group community disappeared [Hamai et al, 1992].…”
Section: Within-community Aggressionmentioning
confidence: 94%
“…Cannibalism by chimpanzees has only been observed in the aftermath of lethal attacks [e.g., Bygott, 1972;Goodall, 1986;Hamai et al, 1992;Watts and Mitani, DOI: 10.1159/000488509 2000]. Chimpanzees rarely scavenge [Gilby et al, 2017] and have never been observed to scavenge conspecifics who have died of natural or accidental causes [Goodall, 1986].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, infanticide by females is usually restricted to the first 2 months after an infant's birth and is likely driven by long-term resource competition, whereby females eliminate a future competitor and gain access to resources that would otherwise be used by the victim [Goodall, 1977;Townsend et al, 2007;Pusey et al, 2008]. Victims of infanticide are frequently cannibalized to some degree and may be shared with family members or group mates [e.g., Bygott, 1972;Goodall, 1977;Nishida et al, 1979;Takahata, 1985;Hamai et al, 1992;Watts and Mitani, 2000]. In contrast, adult victims are only occasionally (and partially) consumed [Goodall, 1986;Pruetz et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should not allow these to hold us back from identifying general patterns in the archaeological record that can, if nothing else, be read to imply the existence of superstitious belief and its origins. Goodall 1977;Norikoshi 1982;Takahata 1985;Hamai et al 1992), the curation of dead infants by their mothers for up to 68 days after death (Biro et al 2010;Matsuzawa 2003), the intellectual and physical investigation of corpses (morbidity) and various examples of social theatre in close proximity to corpses which appears to be occasioned by them (e.g. Bygott 1972;Teleki 1973;Goodall 1977;Boesch and Boesch-Achermann 2000;Anderson et al 2010;Cronin et al 2011).…”
Section: Barrett 2011mentioning
confidence: 99%